mTOR-mediated phosphorylation of VAMP8 and SCFD1 regulates autophagosome maturation - Hong Huang (Nature Portfolio, 2021)
Autophagy relies on coordinated fusion of organelle membranes, although the interplay between the regulatory machinery is not well studied. Here, the authors show that SNARE complex formation is inhibited by mTORC1 phosphorylation of VAMP8, which prevents autophagosome-lysosome fusion.